Упростите выражение. 4b/3(b+1) - b/b+1; 1/a(a+b) + 1/b(a+b); m/4m-4 - m/12m-12. Помогите пожалуйста ребят,девчат*) Срочно нужно.Даю 40 баллов.

Упростите выражение. 4b/3(b+1) - b/b+1; 1/a(a+b) + 1/b(a+b); m/4m-4 - m/12m-12. Помогите пожалуйста ребят,девчат*) Срочно нужно.Даю 40 баллов.
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{4b}{3(b+1)} - \frac{b}{b+1} = \frac{4b-3b}{3(b+1)} = \frac{b}{3(b+1)} [/latex] [latex] \frac{1}{a(a+b)}+ \frac{1}{b(a+b)}=\frac{b+a}{ab(a+b)}= \frac{1}{ab} [/latex] [latex] \frac{m}{4(m-1)}- \frac{m}{12(m-1)}= \frac{3m-m}{12(m-1)}= \frac{2m}{12(m-1)}= \frac{m}{6(m-1)} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы